MALU DALAM KEBAIKAN BERDASARKAN PERSPEKTIF HADITS DAN PSIKOLOGI : Indonesia - Alifah Raudhah; Ujang Rohman; Shalahudin Ismail (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
The purpose of this study is to provide insight and more knowledge about shame in goodness by reviewing it from a hadith and psychological perspectives. The research method used in this study was to conduct interviews with one of the Islamic boarding schools in the East Bandung area and use the library research method. The results obtained from this study are that shame brings goodness if we are ashamed of the right things, and shame is highly recommended even by Rasulullah PBUH because shame will bring us peace of mind, but humans still have to be able to place shame on the right things. Shame is necessary in everyday life to maintain peace of mind, and shame leads us to positive things if we can put ourselves in the face of sham